Late onset pulmonary embolism in young male otherwise healthy COVID-19 patients - M. Karolyi; E. Pawelka; S. Omid; H. Kelani; T. Mader; S. Baumgartner; H. Laferl; M. Traugott; T. Seitz; A. Zoufaly; C. Wenisch (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Effects of prey quality and predator body size on prey DNA detection success in a centipede predator - B. Eitzinger; E. M. Unger; M. Traugott; S. Scheu (Molecular Ecology, 2014)
Predator body size and prey quality are important factors driving prey choice and consumption rates. Both factors might affect prey detection success in PCR ‐based gut content analysis, potentially resulting in over‐ or underestimation of feeding rates. Experimental evidence, however, is scarce. We examined how body size and prey quality affect prey DNA detection success in centipede predators. Due to metabolic rates increasing with body size, we hypothesized that prey DNA detection intervals will be shorter in large predators than in smaller ones. Moreover, we hypothesized that prey detection intervals of high‐quality prey, defined by low carbon‐to‐nitrogen ratio will be shorter than in low‐quality prey due to faster assimilation. Small, medium and large individuals of centipedes L ithobius spp. ( L ithobiidae, C hilopoda) were fed C ollembola and allowed to digest prey for up to 168 h post‐feeding. To test our second hypothesis, medium‐sized lithobiids were fed with either D iptera or L umbricidae. No significant differences in 50% prey DNA detection success time intervals for a 272‐bp prey DNA fragment were found between the predator size groups, indicating that body size does not affect prey DNA detection success. Post‐feeding detection intervals were significantly shorter in Lumbricidae and Diptera compared to Collembola prey, apparently supporting the second hypothesis. However, sensitivity of diagnostic PCR differed between prey types, and quantitative PCR revealed that concentration of targeted DNA varied significantly between prey types. This suggests that both DNA concentration and assay sensitivity need to be considered when assessing prey quality effects on prey DNA detection success.

Endoparasitism in cereal aphids: molecular analysis of a whole parasitoid community - M. TRAUGOTT; J. R. BELL; G. R. BROAD; W. POWELL; F. J. F. VAN VEEN; I. M. G. VOLLHARDT; W. O. C. SYMONDSON (Molecular Ecology, 2008)
Insect parasitoids play a major role in terrestrial food webs as they are highly diverse, exploit a wide range of niches and are capable of affecting host population dynamics. Formidable difficulties are encountered when attempting to quantify host–parasitoid and parasitoid–parasitoid trophic links in diverse parasitoid communities. Here we present a DNA‐based approach to effectively track trophic interactions within an aphid–parasitoid food web, targeting, for the first time, the whole community of parasitoids and hyperparasitods associated with a single host. Using highly specific and sensitive multiplex and singleplex polymerase chain reaction, endoparasitism in the grain aphid Sitobion avenae (F) by 11 parasitoid species was quantified. Out of 1061 aphids collected during 12 weeks in a wheat field, 18.9% were found to be parasitized. Parasitoids responded to the supply of aphids, with the proportion of aphids parasitized increasing monotonically with date, until the aphid population crashed. In addition to eight species of primary parasitoids, DNA from two hyperparasitoid species was detected within 4.1% of the screened aphids, with significant hyperparasitoid pressure on some parasitoid species. In 68.2% of the hyperparasitized aphids, identification of the primary parasitoid host was also possible, allowing us to track species‐specific parasitoid‐hyperparasitoid links. Nine combinations of primary parasitoids within a single host were found, but only 1.6% of all screened aphids were multiparasitized. The potential of this approach to parasitoid food web research is discussed.

INVITED REVIEW: Molecular analysis of predation: a review of best practice for DNA‐based approaches - R. A. KING; D. S. READ; M. TRAUGOTT; W. O. C. SYMONDSON (Molecular Ecology, 2008)
Molecular analysis of predation, through polymerase chain reaction amplification of prey remains within the faeces or digestive systems of predators, is a rapidly growing field, impeded by a lack of readily accessible advice on best practice. Here, we review the techniques used to date and provide guidelines accessible to those new to this field or from a different molecular biology background. Optimization begins with field collection, sample preservation, predator dissection and DNA extraction techniques, all designed to ensure good quality, uncontaminated DNA from semidigested samples. The advantages of nuclear vs. mitochondrial DNA as primer targets are reviewed, along with choice of genes and advice on primer design to maximize specificity and detection periods following ingestion of the prey by the predators. Primer and assay optimization are discussed, including cross‐amplification tests and calibratory feeding experiments. Once primers have been made, the screening of field samples must guard against (through appropriate controls) cross contamination. Multiplex polymerase chain reactions provide a means of screening for many different species simultaneously. We discuss visualization of amplicons on gels, with and without incorporation of fluorescent primers. In more specialized areas, we examine the utility of temperature and denaturing gradient gel electrophoresis to examine responses of predators to prey diversity, and review the potential of quantitative polymerase chain reaction systems to quantify predation. Alternative routes by which prey DNA might get into the guts of a predator (scavenging, secondary predation) are highlighted. We look ahead to new technologies, including microarrays and pyrosequencing, which might one day be applied to this field.

Revealing species‐specific trophic links in soil food webs: molecular identification of scarab predators - A. JUEN; M. TRAUGOTT (Molecular Ecology, 2007)
Soil food webs are particularly important in terrestrial systems, but studying them is difficult. Here we report on the first study to apply a molecular approach to identify species‐specific trophic interactions in below‐ground food webs. To identify the invertebrate predator guild of the garden chafer Phyllopertha horticola (Coleoptera, Scarabaeidae) whose root‐feeding larvae can be highly abundant in grasslands, a specific DNA marker was developed. It allowed detection of P. horticola egg and white grub meals within the gut content of Poecilus versicolor (Coleoptera, Carabidae) larvae for up to 24 h post‐feeding. Soil samples from an alpine grassland revealed a diverse below‐ground macro‐invertebrate community with earthworms, P. horticola larvae, and centipedes as well as beetle larvae as the most abundant detritivores, herbivores, and predators, respectively. Garden chafer DNA was detected in 18.6%, 4.1%, and 4.4% of field‐collected Geophilidae ( n = 124), beetle larvae ( n = 159), and Lithobiidae ( n = 49), respectively. We conclude that most of the investigated predators actively preyed on P. horticola , as secondary predation is unlikely to be detected in below‐ground systems. Moreover, scavenging most likely contributes only to a small percentage of the revealed trophic links due to the low availability of carrion. Sampling date did not influence prey detection rates, indicating that both P. horticola eggs and larvae were preyed on. Only 2.7% of the below‐ground predators tested positive for earthworms, an alternative, highly abundant prey, suggesting that P. horticola represents an important prey source for centipedes and predatory beetle larvae during summer within the soil food web.